A rare case of chronic ectopic pregnancy: a diagnostic enigma - Sadangi, Prativa; Ranjeeta, Kumari; Jena, Manasi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Clinical presentation of chronic ectopic pregnancy is often vague and confusing. Because of this diagnosis becomes delayed and difficult. Here we present one such case, reporting to our hospital. The low resource set up led to limitations in our approach and here we point out the factors which led to the diagnostic dilemma. We are reporting this case because similar challenges can be faced by other clinician in our field.